The Welfare Effects of Globalization with Labor Market Regulation - Tapio K. Palokangas (Institute for the Study of Labor (IZA), 2015)
I examine how globalization affects wages and welfare in a general equilibrium model of international trade with partly oligopolistic markets. Globalization is modeled as reducing trade costs or opening up shielded sectors to trade. There is a national or international common agency that determines minimum wages for the oligopolists, either directly or through supporting labor unions. The lobbies of employers and labor unions influence that agency, relating their prospective political contributions to the latter's decisions. Both a shift from national to international regulation and a decrease in trade costs promote aggregate welfare, but decrease open-sector relative wages.
Keywords: C72; F16; J51; 330; globalization; international trade; common agency; regulation; labor unions